2007
DOI: 10.1189/jlb.1006599
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide induces the synthesis of proinflammatory cytokines in human monocyte cell line U937 via the ERK-NF-κB pathway

Abstract: Hydrogen sulfide (H2S) is now considered an endogenous, gaseous mediator, which has been demonstrated to be involved in many inflammatory states. However, the mechanism of its proinflammatory function remains unknown. In the present study, we used IFN-gamma-primed human monocytic cell line U937 to investigate the effects of H2S in vitro on monocytes. We found that treatment with the H2S donor, sodium hydrosulfide, led to significant increases in the mRNA expression and protein production of TNF-alpha, IL-1beta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
111
2
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 158 publications
(123 citation statements)
references
References 56 publications
7
111
2
3
Order By: Relevance
“…The ERK1/2 activation has been shown to be increased (42)(43)(44)(45)(46), decreased (22,23,29,(47)(48)(49) or unaltered (50,51) following exposure to H 2 S. In the present study, we provide clear evidence that the activation of ERK1/2 contributes to HG-induced injury in H9c2 cells and that exogenous H 2 S protects H9c2 cells against HG-induced injury by inhibiting ERK1/2 activation, which is supported by our previous study [Dong et al (23)]. Although the mechanisms through which ERK1/2 induces either cell death or survival and the reasons for the differential effects induced by exogenous H 2 S on the activation of ERK1/2 are unclear, it is generally accepted that the duration and magnitude of ERK1/2 activation may be an important factor in determining cell survival or apoptosis (52).…”
Section: Discussionmentioning
confidence: 99%
“…The ERK1/2 activation has been shown to be increased (42)(43)(44)(45)(46), decreased (22,23,29,(47)(48)(49) or unaltered (50,51) following exposure to H 2 S. In the present study, we provide clear evidence that the activation of ERK1/2 contributes to HG-induced injury in H9c2 cells and that exogenous H 2 S protects H9c2 cells against HG-induced injury by inhibiting ERK1/2 activation, which is supported by our previous study [Dong et al (23)]. Although the mechanisms through which ERK1/2 induces either cell death or survival and the reasons for the differential effects induced by exogenous H 2 S on the activation of ERK1/2 are unclear, it is generally accepted that the duration and magnitude of ERK1/2 activation may be an important factor in determining cell survival or apoptosis (52).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that MAPKs and NF-κB pathways were involved in LPSinduced up-regulation of cPLA 2 (Luo et al, 2006). Moreover, MAPKs are reported to mediate both cPLA 2 expression, and phosphorylation (Zhi et al, 2007). Several lines of evidence demonstrate that various stimulators beside LPS induce the expression of cPLA 2 through MAPK activation.…”
Section: Discussionmentioning
confidence: 99%
“…The transcriptional dependence of MIP-2 and MCP-1 on NF-B was confirmed with a specific NF-B inhibitor, Bay 11-7082. Bay 11-7082 selectively and irreversibly prevents IB␣ phosphorylation, which disrupts NF-B function by sparing IB␣ from proteasomal degradation, thereby permitting it to bind to and inactivate NF-B (33,45). Pretreatment with Bay 11-7082 diminished the chemokine responses induced by SP, which reinforced NF-B as the main transcriptional regulator involved.…”
Section: Discussionmentioning
confidence: 99%